2015
DOI: 10.1136/annrheumdis-2015-eular.5395
|View full text |Cite
|
Sign up to set email alerts
|

AB0877 Effectiveness of Intra-Articular Injection of Platelet-Rich Plasma on Clinical Improvement of Patients with Knee Osteoarthritis

Abstract: BackgroundPlatelet-rich plasma (PRP), an autologous source of growth factors, can stimulate stem cells and chondrocytes within synovial joints to enhance cartilage regeneration of patients with osteoarthritis (OA).1ObjectivesTo evaluate the effectiveness of intra-articular injection of PRP on clinical improvement of patients with knee OA.MethodsDuring March to December 2013 patients who visited the Rheumatolgy Clinic in Imam Reza Hospital, Mashhad, Iran, with diagnosis of knee OA were interviewed and examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The current study effectiveness results are comparable with the recently published results by several RCTs reporting clinical results in patients with knee OA treated with IA injections. A recent study by Jalal Jivan S et al compared the effectiveness of IA injection of platelet-rich plasma (PRP) with HA (as one of the standard treatments) on mild to moderate knee OA (13). They found that in the majority of visits (especially 6 and 12 month), the extent of improvement in scores of KOOS subscales was signi cantly higher in the PRP recipients, compared to that in the HA recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The current study effectiveness results are comparable with the recently published results by several RCTs reporting clinical results in patients with knee OA treated with IA injections. A recent study by Jalal Jivan S et al compared the effectiveness of IA injection of platelet-rich plasma (PRP) with HA (as one of the standard treatments) on mild to moderate knee OA (13). They found that in the majority of visits (especially 6 and 12 month), the extent of improvement in scores of KOOS subscales was signi cantly higher in the PRP recipients, compared to that in the HA recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous PRP has always been the choice of treatment as it is inherently biocompatible, safe and free from the risk of acquiring microbial and viral transmissible infections [Lacci and Dardik, 2010;Li and Li, 2013]. Several published phase I/II clinical trials have firmly demonstrated the superiority of autologous PRP in comparison to using hyaluronic acid [Cole et al, 2017;Jubert et al, 2017;Raeissadat et al, 2017;Glynn et al, 2018;Taniguchi et al, 2018;Di Martino et al, 2019;Jalali et al, 2021;Nie et al, 2021]. A single injection of autologous PRP into class I obese older patients (with the mean age of 67 years) was reported to be useful in relieving pain in the late-stage knee OA.…”
Section: Introductionmentioning
confidence: 99%